BIODIESEL PRODUCTION FROM MICROWAVE IRRADIATED REACTOR USING HOMOGENEOUS AND HETEROGENEOUS CATALYSIS - Rabelo, S. N.; Oliveira, L. S.; França, A. S. (Revista de Engenharia Térmica, 2018)
Biodiesel was successful produced in a microwave irradiation reactor using homogeneous and heterogeneous catalysis. The biodiesel was production by the trasesterification reaction of soybean oil using metanol. Sodium methylate (30% solution in metanol) was used for the homogeneous catalyst and the heterogeneous catalyst was developed using wasted eggshells. The eggshells were calcined and tested pure and doped with potassium hydroxide in 10, 30 and 50% of weight. The power and temperature of the microwave were kept constant in every reaction being 800W and 200º Celsius, respectively. The reaction time was significantly reduced using microwave compared to the conventional process. In only one minute of reaction, the methyl ester (FAME) conversion obtained was 98.9% with the homogeneous catalyst and within 15 minutes, the heterogeneous catalysis accomplished 100%. For heterogeneous catalyst, the best results were acquired when the doped catalyst contained 50% of KOH. The results indicated that the eggshells treated with KOH has a great potential to be used for microwave-assisted transesterification reactions of oils with mild operations conditions: molar ratio oil/alcochol 1:6 and just 5% of catalyst. In addition, the heterogenous catalyst was recovered and reused in other reactions with a relatively satisfying results. The physico-chemical properties of the catalysts were characterized by X-ray diffraction and thermogravimectric analysis.